2020
DOI: 10.1101/2020.01.30.927392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary Evidence of the role of estrogen and tamoxifen-induced regulation of complement proteins in rat hippocampus

Abstract: Effects of Estrogen (E2) is widespread in the human body; still, an unresolved paradox.Neurodegeneration and neuroinflammation are inherently associated with age progression, debilitating by hormone deprivation, especially in female. Senescent cells accumulate with age and promote tissue deterioration in the body system. Neurodegenerative diseases drive a healthy life towards to morbidity and feebleness; despite the different etiology, uncontrolled inflammation is one of the significant causals factors. We her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Estrogen/estrogen receptor-β signaling elevates AKR1C3 expression, and it has been previously shown that estrogenic tumors are heavily infiltrated by M2-polarized microglia and macrophages [ 1 , 31 ]. Estrogen is known to elevate CCL18 secretion in M2 macrophages [ 51 ], but it downregulates the expression of complement components, including C3, in normal brain tissue [ 52 ]. A recent study demonstrated that CCL18 released by GBM-infiltrating microglia/macrophages promotes glioma growth [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen/estrogen receptor-β signaling elevates AKR1C3 expression, and it has been previously shown that estrogenic tumors are heavily infiltrated by M2-polarized microglia and macrophages [ 1 , 31 ]. Estrogen is known to elevate CCL18 secretion in M2 macrophages [ 51 ], but it downregulates the expression of complement components, including C3, in normal brain tissue [ 52 ]. A recent study demonstrated that CCL18 released by GBM-infiltrating microglia/macrophages promotes glioma growth [ 53 ].…”
Section: Introductionmentioning
confidence: 99%